2015
DOI: 10.1016/j.nimb.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Online coupling of pure O2 thermo-optical methods – 14C AMS for source apportionment of carbonaceous aerosols

Abstract: This paper reports on novel separation methods developed for the direct determination of 14 C in organic carbon (OC) and elemental carbon (EC), two sub-fractions of total carbon (TC) of atmospheric air particulate matter. Until recently, separation of OC and EC has been performed off-line by manual and time-consuming techniques that relied on the collection of massive CO2fractions. We present here two on-line hyphenated techniques between a Sunset OC/EC analyzer and a MICADAS (MIni radioCArbon DAting System) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 12 publications
2
43
0
Order By: Relevance
“…Based on the instrumentation setup described in Agrios et al (2015) and on the method described in Zotter et al (2014b), radiocarbon analysis of TC and EC was conducted on a set of 33 filters. The 14 C content of blank filters was measured for TC only, as there was no EC found on these filters.…”
Section: C Analysismentioning
confidence: 99%
“…Based on the instrumentation setup described in Agrios et al (2015) and on the method described in Zotter et al (2014b), radiocarbon analysis of TC and EC was conducted on a set of 33 filters. The 14 C content of blank filters was measured for TC only, as there was no EC found on these filters.…”
Section: C Analysismentioning
confidence: 99%
“…2). Recently the Sunset instrument was directly coupled to the zeolite trap of the GIS , which allows online 14 C measurements of the carbonaceous fractions separated in the Sunset system (Agrios et al, 2015). When combusted, the gaseous carbonaceous species pass through a MnO 2 bed heated to 850 • C for completing the oxidation to CO 2 , which is further transported by helium to the zeolite trap.…”
Section: Recent Optimisation In Oc/ec Separation and Ams Analysismentioning
confidence: 99%
“…Further the preparation and measurement time is significantly reduced because there is no need for offline combustion, resulting in a total measurement time of approximately 35 min per sample only. In addition, it not only allows for an automated protocol of standard injection for AMS calibration, but also offers the possibility for easy and regular (daily) survey of the 14 C background in the entire process line (Sunset-GIS-AMS) by analysis of variably sized standards and blanks if required (Agrios et al, 2015). Finally, the Sunset system enables continuous monitoring of the combustion process, reducing a potential bias due to charring, and the standardised and automated combustion protocol (Swiss 4S) ensures high reproducibility increasing the overall precision.…”
Section: Recent Optimisation In Oc/ec Separation and Ams Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have revealed that organic matter (OM) is the largest fraction of ambient fine particles, typically comprising 20-90 % of the submicron particulate mass . Factor analysis of aerosol mass spectra from the Aerodyne aerosol mass spectrometer enables the deconvolution of OM into different factors based on their mass spectral fingerprints (Lanz et al, 2007;Aiken et al, 2009;Ulbrich et al, 2009). Such results provided valuable insights into the source and transformation processes of organic aerosols (OA) in the atmosphere (Lanz et al, 2010;Ng et al, 2011;Hildebrandt et al, 2011;Canonaco et al, 2013;Bougiatioti et al, 2014;Huang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%